2017
DOI: 10.1590/0103-8478cr20151535
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi and colonization stimulant in cotton and maize

Abstract: The objective of this study was to evaluate the effects of inoculation with different arbuscular mycorrhizal fungi native to Cerrado, associated with the application of colonization stimulant (7-hydroxy, 4’-methoxy-isoflavone) at the initial growth of cotton and maize plants in a greenhouse. The experiment was carried out in a completely randomized design and 7x2 factorial scheme, with five species of arbuscular mycorrhizal fungi and combined inoculation (uniting all species in equal proportion) and native fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
2
7
0
1
Order By: Relevance
“…The positive effects of the isoflavonoid formononetin on AMF colonization agrees with several studies that confirmed its potential to stimulate mycorrhization (Silva-Júnior and Siqueira, 1997;Siqueira et al, 1999;Soares and Martins, 2000;Catford et al, 2006;Cordeiro et al, 2015;Castillo et al, 2014;Ribeiro et al, 2016;Salgado et al, 2017;Savana da Silva et al, 2017). Some phenolic compounds are known to have an effect on different types of symbiosis in plants, such as formononetin of mycorrhiza (Siqueira, Safir and Nair, 1991).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The positive effects of the isoflavonoid formononetin on AMF colonization agrees with several studies that confirmed its potential to stimulate mycorrhization (Silva-Júnior and Siqueira, 1997;Siqueira et al, 1999;Soares and Martins, 2000;Catford et al, 2006;Cordeiro et al, 2015;Castillo et al, 2014;Ribeiro et al, 2016;Salgado et al, 2017;Savana da Silva et al, 2017). Some phenolic compounds are known to have an effect on different types of symbiosis in plants, such as formononetin of mycorrhiza (Siqueira, Safir and Nair, 1991).…”
Section: Discussionsupporting
confidence: 86%
“…Savana da Silva et al, (2017) verified a positive effect of formononetin applied as seed treatment in soybean, increasing the infection of root nodules by AMF, thus forming a tripartite symbiosis. Field trials also reported increased yields using this product (Myconate) as seed treatments (Peixe et al, 2013;Santos, 2014;Cordeiro et al, 2015;Ribeiro et al, 2016;Salgado et al, 2017). Ribeiro et al, (2016) also reported an increase in soybean yield, mycorrhization and nodulation with the use of formononetin as seed treatment, indicating a rate above 50 g.ha -1 to be applied as seed treatment.…”
Section: Formononetinmentioning
confidence: 98%
See 1 more Smart Citation
“…The transfer of this model to more crops is under investigation [18]. Similarly, mycobacteria and mycorrhizal fungi play a symbiotic role in supporting phosphate uptake by solubilizing phosphate [19,20]. Better use of the soil microbiome reduces fertilizer requirements and the ecological footprint of crop production.…”
Section: Biotechnology and Sustainable Biomass Productionmentioning
confidence: 99%
“…They stated that AM fungus inoculation along with RP amendment could substitute chemical fertilizers and rendered the P in RP available to the plants. Salgado et al (2017) measured shoots dry matter (SDM), roots dry matter (RDM), mycorrhizal colonization and accumulation of calcium, zinc and phosphorus in the SDM at maize flowering in response to inoculation with five different arbuscular mycorrhizal fungi at Cerrado, Brazil. They concluded that inoculation with mycorrhizal fungi demonstrated different effects for the various parameters evaluated in maize.…”
Section: Introductionmentioning
confidence: 99%